2021
DOI: 10.3390/nano11020341
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Iron on the Fe–Co–Ni Ternary Nanocomposites Structural and Magnetic Features Obtained via Chemical Precipitation Followed by Reduction Process for Various Magnetically Coupled Devices Applications

Abstract: This paper presents the synthesis of Fe–Co–Ni nanocomposites by chemical precipitation, followed by a reduction process. It was found that the influence of the chemical composition and reduction temperature greatly alters the phase formation, its structures, particle size distribution, and magnetic properties of Fe–Co–Ni nanocomposites. The initial hydroxides of Fe–Co–Ni combinations were prepared by the co-precipitation method from nitrate precursors and precipitated using alkali. The reduction process was ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…The resulting composite surpasses the restrictions of separate parts by combining the unique traits of each material, providing properties that make it well-suited for specific applications. Ternary nanocomposites have various multifunctional features, including great mechanical strength, exceptional redox reactivity, excellent electrical conductivity, a large surface area, and exceptional catalytic activity [79][80]. Because of these qualities, ternary nanocomposite was preferred over single or dual nanomaterials.…”
Section: Ternary Nanocomposite For Biosensor Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The resulting composite surpasses the restrictions of separate parts by combining the unique traits of each material, providing properties that make it well-suited for specific applications. Ternary nanocomposites have various multifunctional features, including great mechanical strength, exceptional redox reactivity, excellent electrical conductivity, a large surface area, and exceptional catalytic activity [79][80]. Because of these qualities, ternary nanocomposite was preferred over single or dual nanomaterials.…”
Section: Ternary Nanocomposite For Biosensor Developmentmentioning
confidence: 99%
“…Using one or two nanoparticles for biosensor design instead of ternary nanocomposites may have the following disadvantages: i) Restricted functionality: Unlike ternary nanocomposites, one or two nanomaterials may have limited functions or properties. Ternary nanocomposites can integrate the various properties of three different nanomaterials, resulting in a broader range of properties such as enhanced conductivity, catalytic activity, or binding abilities [79][80]. This functional constraint may reduce the biosensor's sensing capacity and overall performance.…”
Section: Ternary Nanocomposite For Biosensor Developmentmentioning
confidence: 99%
“…This is with regard to any material property of the nanocomposites, be it related to crystallographic and/or electronic structure. In line with this theme, eight representative articles [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 ] have been published in this Special Issue:…”
mentioning
confidence: 97%
“…Karunakaran et al [ 2 ] reported the synthesis of Fe–Co–Ni ternary nanocomposites obtained by co-precipitation and followed by hydrogen reduction, and the effect of Fe content on the consequent magnetic properties (as a first report). Initial hydroxides of Fe-Co–Ni combinations were prepared by the co-precipitation method from nitrate precursors and precipitated using alkali.…”
mentioning
confidence: 99%